PENGGUNAAN LEMBAR KERJA PESERTA DIDIK (LKPD) KOMIK UNTUK MENINGKATKANPRESTASI BELAJARPESERTA DIDIK PADA POKOK BAHASAN REAKSI REDUKSI DANOKSIDASI DI KELAS X MIA MAN 2 MODEL PEKANBARU - Anggi Desviana Siregar Desviana Siregar; Rini '; Herdini ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract:The research aims to improve the achievement of learners on the subject of Reduction and Oxidation Reaction in class X MAN 2 MODEL MIA Pekanbaru. The research is a kind of experiment research with pretest-posttest design.  Research conducted in MAN 2 MODEL Pekanbaru. The samples of this research were the students of class X4 as the experimental class and students of class X1 as the control class randomly determined after the tests of normality and homogeneity test. The learning process at experimental class and control class based scientific approach to the curriculum in 2013. Experimental class is a class that is applied to LKPD comic while the control class was not. Data analysis technique used is the t-test. Based on data analysis of data obtained tcount> ttable is 3.18 >1.67, means  that the use of LKPD comic can improve student learning achievement on the subject of Reduction and Oxidation Reaction in class X MAN 2 MODEL MIA Pekanbaru. The category improvement of student achievement at experiment class was high category with N-gain normalized is 0,81. Meanwhile, the category improvement of student achievement in control class was medium category with N-gain normalized is 0,68. Keywords : Learning Achievement, LKPD Comic, and Reduction and Oxidation Reaction